Evaluation of the Insulinotrophic Activity of Malaysian Traditional Plants Extract - Hamid, Muhajir; Mohd Bohari, Siti Pauliena; Bastami, Mohd Saufi; Ali, Abdul Manaf; Mustapha, Nik Musa'adah; Shari, Khozirah (Asian Network for Scientific Information, 2008)
In this study, methanolic extracts of 14 traditional plants in Malaysia were screened for insulinotrophic properties, using rat pancreatic B-cell lines, BRIN-BD11 cells. In 30min acute static incubation test, all 14 plants showed varying degree of responsivess in insulin release with Labisa pumila, Morinda charantia and Tinospora crispa having high insulinotrophic activities. These plants also displayed appreciably low cyotoxic activities. These results show a promising avenue for development of novel insulin secretagogues.